Working conditions in global value chains: Evidence for European employees - Dagmara Nikulin; Joanna Wolszczak-Derlacz; Aleksandra Parteka (Gdańsk University of Technology, Faculty of Management and Economics, 2019)
This paper investigates how involvement in Global Value Chains (GVCs) affects working conditions. We use linked employer-employee data from the Structure of Earnings Survey merged with industry-level statistics on GVCs based on the World Input-Output Database. The sample consists of almost 9 million workers in 24 European countries in 2014. Given the multidimensional nature of the dependent variable, we compare the estimates resulting from a Mincerian wage model with zero-inflated negative binomial regressions that analyse other aspects of working conditions (overtime work and bonus payments). As to the impact of production fragmentation on social upgrading, wages prove to be negatively related to sectoral GVC involvement. Workers in sectors more deeply involved in GVCs have lower and less stable earnings, meaning worse working conditions; on the other hand, they are also less likely to have to work overtime, which one may see as a sign of better labour standards
Keywords: F16; F66; J81; 330; working conditions; Global Value Chains; wellbeing of workers; social upgrading